The public’s antibiotic use behavioural patterns and their determinants for upper respiratory tract infections: a latent class analysis based on consumer behaviour model in China - Lin, Rujiao; Duan, Lixia; Liu, Chaojie; Wang, Dan; Zhang, Xinping; Wang, Xi; Zhang, Xinyi; Wang, Qianning; Zheng, Shuangjiang; Liu, Chenxi (Frontiers in Public Health, 2023)
Background: The irrational use of antibiotics among the public is a major contributor to antibiotic resistance, which is a serious global threat. Prior studies have demonstrated that there are different behavioural patterns regarding antibiotic use among the public, and targeted interventions for subgroups with different behavioural patterns may be more effective. Thus, this study aimed to identify the public’s behavioural patterns of antibiotic use for upper respiratory tract infections (URTIs) and their influencing factors. Methods: A cross-sectional survey was conducted among the general population in Chongqing, China. Consumer decision-making (Consumer Behaviour Model, CBM) was used to assess the public’s behaviours regarding antibiotic use, including need recognition, information searching, alternative evaluation, obtaining antibiotics, antibiotic consumption, and postuse evaluation. Furthermore, a latent class analysis was used to identify the underlying behavioural patterns among the public. The identified behavioural patterns of antibiotic use were further linked with individuals’ capacity, opportunity, and motivation factors of antibiotic use based on a multinominal logistic regression to explore possible determinants. Results: A total of 815 respondents were enrolled in the study. The public’s irrational use of antibiotics was prevalent, including antibiotic self-medication (39.63%), nonprescription antibiotic purchasing (59.02%), and early stopping of antibiotic prescriptions (76.56%). Four behavioural patterns regarding antibiotic use for URTIs were identified, namely, “antibiotic self-medicators”, “formal health care seekers”, “various treatment users”, and “self-medication without antibiotics”. Individuals’ self-efficacy of antibiotic use, belief in antibiotic effectiveness, awareness of antibiotic side effects, perceived antibiotic availability, social influence, and demographics (age, gender, and education) were significantly associated with the public’s different behavioural patterns of antibiotic use for URTIs. Conclusion: This study calls for collaborative efforts among the public, physicians, policy makers, and the implementation of precise and multifaceted interventions to effectively reduce irrational use of antibiotics in the public. Such interventions include identifying subgroups within the public to provide more targeted education about antibiotics and the management of URTIs, reinforcing the regulation of antibiotic dispensing, and improving physicians’ rational antibiotic prescriptions.